Intelectuais e política: a trajetória do Tribunal Internacional de Crimes de Guerra (1966-1967) - Santos, Júlio Antônio Bonatti [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This work discusses the historical role of intellectuals in politics based on the analysis of the trajectory of the International War Crimes Tribunal, later known as Russell Tribunal, created to judge crimes against humanity committed by north-american imperialism in Vietnam War. We seek to discern the importance of intellectuals in the tableau of international power, in order to identify their role as a social group that raises his voice, mainly against the crimes of silence. In other words, we conceive the intellectual not as a person who merely produces knowledge, but as one who denounces the injustices happening in the world, especially those who do not find a real punishment. Therefore, the Russell Tribunal reiterates and updates the value assumed by the identity category of intellectuals in contemporary societies since the “Affaire Dreyfus”, which occurred in France in the late nineteenth century, to the present day. This symbolic demarcation is here investigated, indeed, by understanding the meanings and possibilities of the discourse of intellectuals who were involved in the international debate established and encouraged by the Russell Tribunal

A presente dissertação pretende discutir o papel histórico dos intelectuais na política a partir da análise da trajetória do Tribunal Internacional de Crimes de Guerra, posteriormente conhecido como Tribunal Russell, criado para julgar os crimes contra a Humanidade cometidos pelo imperialismo norte-americano na Guerra do Vietnã. Busca-se divisar a importância dos intelectuais no jogo do poder internacional, no sentido de identificar o seu papel como o de um grupo social que levanta a sua “voz”, principalmente, contra os crimes de silêncio, ou seja, pensa-se o intelectual não apenas como o indivíduo que produz conhecimento, mas enquanto aquele que é responsável pela denúncia das injustiças ocorridas no mundo, especialmente as que não encontram a punição aos criminosos. O Tribunal Russell reitera e atualiza o valor identitário assumido pela categoria dos intelectuais nas sociedades contemporâneas desde o caso Dreyfus, ocorrido na França no final do século XIX até os nossos dias. É essa demarcação simbólica que é aqui investigada por meio da reposição dos sentidos e do alcance dos discursos dos intelectuais que se envolveram no palco do debate internacional estabelecido e estimulado pelo Tribunal Russell
Keywords: Intelectuais - História; Intelectuais e politica; Crime contra a humanidade; História política; Crime de guerra; Imperialismo - História - Séc.XX; Vietnã - Historia; Vietnã, Guerra do - 1961-1975; History